SYSTEM FOR WATERING BY MEANS OF ELECTRICALLY HYBRIDISED PHOTOVOLTAIC PUMPING - BARATA CARRELO, Isaac; HOGAN TEVES DE ALMEIDA, Rita; FERNÁNDEZ RAMOS, José; LORENZO PIGUEIRAS, Eduardo; CARRASCO MORENO, Luis Miguel; NARVARTE FERNÁNDEZ, Luis (2018)
The invention relates to a watering system that maximises the use of photovoltaic (PV) solar energy, an electrical grid (10) being connected to the AC entrance (31) of a variable-frequency drive (30) and a PV solar generator (20) being connected to a DC bus (32) of the variable-frequency drive (30) by means of a diode (60) designed to allow electricity to pass in a single direction to the variable-frequency drive (30). According to the invention, the watering system (1) further comprises at least one control unit (70) having an algorithm for tracking the point of maximum power of the PV solar generator (20), the PV solar generator (20) being sized to deliver the power demanded by a water pump (40), such the the voltage at the maximum power point is greater than the DC voltage imposed by the electrical grid (10) on the DC bus (32) of the variable-frequency drive (30). Maximiza el aprovechamiento solar fotovoltaico, donde la red eléctrica (10) está conectada a la entrada alterna (31) del variador de frecuencia (30); el generador solar FV (20) está conectado al bus de continua (32) del variador de frecuencia (30) a través de un diodo (60) adaptado para permitir el paso de corriente eléctrica en un único sentido hacia el variador de frecuencia (30); donde el sistema de riego (1) comprende además al menos una unidad de control (70) que tiene un algoritmo de seguimiento del punto de máxima potencia del generador solar FV (20); estando el generador solar FV (20) dimensionado para entregar la potencia demandada por la bomba de agua (40), tal que su tensión en el punto de máxima potencia es mayor que la tensión DC impuesta por la red eléctrica (10) en el bus de continua (32) del variador de frecuencia (30). L'invention concerne un système d'arrosage qui permet d'exploiter au maximum l'énergie solaire photovoltaïque et qui comprend un réseau électrique (10) connecté à l'entrée de courant alternatif (31) d'un variateur de fréquence (30); un générateur solaire photovoltaïque (20) connecté au bus continu (32) du variateur de fréquence (30) au moyen d'une diode (60) conçue pour permettre le passage de courant électrique dans un sens unique vers le variateur de fréquence (30). Ledit système d'arrosage (1) comprend également au moins une unité de commande (70) qui comporte un algorithme de recherche du point maximal de puissance du générateur solaire photovoltaïque (20). Le générateur solaire photovoltaïque (20) est dimensionné de façon à distribuer la puissance demandée par la pompe à eau (40), de façon que sa tension au point maximal de puissance est supérieure à la tension CC imposée par le réseau électrique (10) dans le bus continu (32) du variateur de fréquence (30).